An investigation of UTHM undergraduates’ reading habits through a pilot study - Sadeq Alsaeedi, Zubaidah; Md. Ngadiran, Nurizah; Abdul Kadir, Zulida (Development in Language Studies, 2022)
Reading is inextricably linked to student success in education and the overall improvement of the human being. The significant decline in leisure reading habits among university students created the impetus for this study.  The purpose of this study was to investigate the general reading habits and reading medium preference among UTHM undergraduates. Data were collected with an online survey sent to students across faculties. A total of 50 students completed the survey. The findings showed that the majority of students read between 30 minutes-1 hour per day and online reading materials (websites) were the most popular type of materials students read. University students' reading habits have changed to new venues as Internet technology has advanced, with online reading being the medium of choice.